Pemanfaatan Aplikasi mathsolver sebagai Media Belajar Matematika - Fadhilah Rahmah; Yahfizam Yahfizam (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Mathematics education in Indonesia still faces various challenges, one of which is students’ low conceptual understanding due to predominantly conventional teaching methods. Amid the advancement of digital technology, the MathSolver application emerges as an alternative solution to assist students in understanding mathematical material through its automatic problem-solving feature and step-by-step explanations. This study aims to examine the utilization of the MathSolver application as a mathematics learning medium using a literature review approach. Data sources were obtained from relevant journals or scientific articles published between 2018 and 2024. The review findings indicate that the use of MathSolver can enhance students' conceptual understanding, support independent learning, and increase motivation to learn mathematics. However, there is also a risk of misuse, where students may rely on the application merely to obtain answers without understanding the underlying processes. Therefore, active teacher involvement is essential to guide the wise use of such applications. In conclusion, MathSolver holds significant potential as an effective and adaptive learning tool in the digital era.